2019
DOI: 10.1002/cam4.2447
|View full text |Cite
|
Sign up to set email alerts
|

Expression significance and potential mechanism of hypoxia‐inducible factor 1 alpha in patients with myelodysplastic syndromes

Abstract: Objective To investigate the expression level and potential mechanism of hypoxia‐inducible factor 1 alpha (HIF‐1α) in patients with myelodysplastic syndromes (MDS). Methods Immunohistochemistry (IHC) techniques were used to examine the protein expression of HIF‐1α in paraffin‐embedded myeloid tissues from 82 patients with MDS and 33 controls (patients with lymphoma that is not invading myeloid tissues). In addition, the associations between the protein expression of HIF‐1α and clinical parameters were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
5
0
1
Order By: Relevance
“…Several genes that define normal blood cells are regulated by miRNAs, and MDS prognosis is linked to certain miRNAs of the bone marrow, peripheral blood, and mononuclear cells ( 69 ). In fact, some CEP55 -controlling miRNAs identified in our in silico model have been listed as differentially expressed in other patients with MDS ( 70 , 71 , 81 , 82 ).…”
Section: Discussionmentioning
confidence: 93%
“…Several genes that define normal blood cells are regulated by miRNAs, and MDS prognosis is linked to certain miRNAs of the bone marrow, peripheral blood, and mononuclear cells ( 69 ). In fact, some CEP55 -controlling miRNAs identified in our in silico model have been listed as differentially expressed in other patients with MDS ( 70 , 71 , 81 , 82 ).…”
Section: Discussionmentioning
confidence: 93%
“…Our data show that proliferation of immature JMML cells is mainly due to hypoxic conditions, suggesting that low oxygen tension is an essential feature for the preservation of the leukemic cell status. It has been demonstrated that HIF-1α expression and its stabilization into nuclei is peculiar of stem cells in MDS, supporting leukemia cell proliferation and self-renewal [44] and that this could represent a promising therapeutic target [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we have not yet found research reports on the exact mechanism of the specific regulatory relationship between miR-93-5p and VEGF . However, after predicting target genes through the TargetScan Human database ( http://www.targetscan.org ), we discovered that miRNA-93 might be targeting hypoxia-inducible factor 1 α ( HIF-1α ) affecting the expression of VEGF [ 61 ]. At the same time, studies have found that the miRNA-93 consensus sequence also exists in the 3′UTR region of VEGF mRNA, which inspires our next research: miRNA-93 may mediate the occurrence development of AML by regulating the expression of HIF-1α/VEGF [ 22 ].…”
Section: Discussionmentioning
confidence: 99%